Management of financial and accounting and analytical support at small and medium-sized enterprises using the «AXIM» system - Yaroshevska, O.; Krasnostup, V.; Ksenofontov, D. (Економічний вісник Донбасу, 2024)
Topicality. The desire to electronize daily routine processes comes into all spheres of human life: education, entertainment, business, everyday life, etc. It is known that automation of any process not only simplifies human work, but also reduces the time for its execution and improves the quality and effectiveness of this operation. Today, more and more mechanical, monotonous work of people is performed by an automatic or automated system. This is justified by the fact that computer software products perform operations much faster and better than humans. Aim and tasks. Study of the features of development and implementation of the automated accounting system “AXIM” with wide functionality for a small enterprise. Conducted content analysis of literary sources of the economic direction and the programming sphere – to select indicators that affect the functioning of the store, study their relationships to develop a software product for increasing the efficiency of trading company business processes; comparative analysis – to reveal the essence and features of software products implementation to improve the efficiency of trading company business processes; analysis and synthesis techniques – to form a system of indicators for the effectiveness of the software product implementation. Research results. An “AXIM” automated system for selling retail goods has been created, which has great functionality and successfully fulfills its tasks. The software product was introduced and tested at the small trading company “Bonus” of individual entrepreneur L. Yakovlieva, which is located in the township Smolino of the Kirovohrad region Malovyskivskyi district. Conclusions. The introduction of the created software product at the investigated small trading company “Bonus” of individual entrepreneur L. Yakovlieva showed effective usage indicators and made it possible to streamline the accounting, simplify the search for product information, automate the scheme of goods sale and control the goods balance in the store. Актуальність. Прагнення електронізувати щоденні рутинні процеси приходить у всі сфери людського життя: побут, освіта, розваги, бізнес тощо. Як відомо, автоматизація будь-якого процесу не тільки спрощує роботу людини, а й зменшує час на її виконання та покращує якість та ефективність цієї операції. На сьогоднішній день все частіше механічну, монотонну роботу людей виконує автоматична чи автоматизована система. Це виправдано тим, що комп’ютерні програмні продукти виконують операції набагато швидше і якісніше, ніж людина. Мета та завдання. Дослідження особливостей розробки та впровадження автоматизованої системи обліку «AXIM» з широкими функціональними можливостями для невеликого підприємства. Проведений контент-аналіз літературних джерел економічного спрямування та сфери програмування – для відбору показників, що впливають на функціонування магазину, вивчення їх взаємозв’язків для розробки програмного продукту задля підвищення ефективності бізнес-процесів торговельного підприємства; порівняльний аналіз – для розкриття сутності та особливостей впровадження програмних продуктів для підвищення ефективності бізнес-процесів торговельного підприємства; прийоми аналізу та синтезу – для формування системи показників з ефективності впровадження програмного продукту. Результати. Створено автоматизовану систему для продажу товарів роздрібної торгівлі «AXIM», яка має великий функціонал та успішно виконує поставлені перед нею задачі. Програмний продукт був впроваджений та апробований на невеликому торговому підприємстві «Бонус» ФОП Л. Яковлєва, яке знаходиться в ОТГ Смоліне Маловисківського району Кіровоградської області. Висновки. Впровадження розробленого програмного продукту на досліджуваному малому підприємстві «Бонус» ФОП Л. Яковлєва показало ефективні показники використання та дозволило упорядкувати облік, полегшити пошук інформації по товарам, автоматизувати схему продажу товару та вести контроль залишку товарів в магазині.